TOLSTOY AND ISLAMIC PHILOSOPHY - Mahsuma Ruzmatjonova (Academia Science Repository, 2023)
The author in this article describes the moral, aesthetic and philosophical origins of the teachings of Tolstoy, which was formed, in part, under the influence of the ideas of Islamic dogma. The author, using the example of some of the author’s works, shows a close connection with Tolstoy’s worldview and Islamic teachings.